Convexity of Certain q-Integral Operators of p-Valent Functions - K. A. Selvakumaran; S. D. Purohit; Aydin Secer; Mustafa Bayram (Abstract and Applied Analysis)
By applying the concept (and theory) of fractional q-calculus, we first define and introduce two new q-integral operators for certain analytic functions defined in the unit disc 𝒰. Convexity properties of these q-integral operators on some classes of analytic functions defined by a linear multiplier fractional q-differintegral operator are studied. Special cases of the main results are also mentioned.